La topographie et les fortifications celtiques de l’oppidum biturige de Châteaumeillant-Mediolanum (Cher) - Sophie Krausz (Revue Archéologique du Centre de la France)
The oppidum of Châteaumeillant is one of the major enclosed sites in the civitas of the Bituriges Cubi. Situated on the route between Argentomagus and Néris-Les-Bains, it still has an impressive fortification which attains almost 12 m in height. This rampart occupies the southern extremity of an inland promontory of 60 hectares set between two stream courses. The La Tène occupation seems however to be restricted to an area of some 24 hectares at the highest, southern part of the promontory. The rampart was excavated between 1957 and 1961 by E. Hugoniot and Jacques Gourvest who identified two successive structures: first a murus gallicus and then a massive dump bank. New excavations from 2001 have confirmed the presence of this substantial fortification, and have shown that it is fronted by a very wide (40 m) flat-bottomed ditch. Whilst the murus gallicus, constructed around 100 BC, seems to have been designed as a symbolic limit to the oppidum, the extra-high dump was defensive in intent. It was probably built during the Gallic War.